SBS mitigation in a microstructured optical fiber by periodically varying the core diameter - Stiller, Birgit; Kudlinski, Alexandre; Lee, Min Won; Bouwmans, Geraud; Delque, Michael; Beugnot, Jean-Charles; Maillotte, Herve; Sylvestre, Thibaut (IEEE Photonics Technology Letters, 2012)
In this letter, we experimentally demonstrate a 4-dB increase of the stimulated Brillouin scattering threshold in a microstructured optical fiber. This result is obtained by periodically varying the size of the air-hole structure by only 7% amplitude, while keeping a low attenuation coefficient. The efficiency of this passive technique is verified by use of the Brillouin echoes-distributed sensing technique where the Brillouin frequency-shift oscillation is clearly observed. © 1989-2012 IEEE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin threshold; distributed Brillouin measurement; microstructured optical fiber; stimulated Brillouin scattering